Periapical status and prevalence of apical periodontitis in patients with type 2 Diabetes mellitus (Research, Society and Development, 2021)
Diabetes mellitus (DM) is a chronic systemic disease that affects the immunoinflammatory response, leading the patient more susceptible to the development of oral diseases, such as apical periodontitis (AP). Thus, this study aimed to clinically and radiographically analyze the periapical status and prevalence of AP in diabetic patients compared to healthy patients. A total of 100 patients were selected and divided into two groups (n = 50): diabetic group - patients with type 2 DM, and control group - systemically healthy patients. Periapical status was analyzed by the periapical index. The quality of the root canal filling and restoration was also evaluated. Difference between the prevalence of AP among the groups were performed by using the Chi-square test or Fisher's exact test (p < 0.05). The total number of teeth was lower in diabetic group (p = 0.049). Teeth without previous endodontic treatment with AP were higher in diabetic group (p = 0.006). However, the number of endodontically treated teeth with AP was greater in the control group (p = 0.027). AP in teeth with previous endodontic treatment was associated with unsatisfactory root canal filling and restoration quality (p < 0.01). The presence of pain showed significantly higher values in the diabetic group (p = 0.003). In conclusion, this study showed an association between the presence of AP and DM in cases of teeth without endodontic treatment. Besides, the presence of pain was significantly higher in diabetic patients. However, healthy patients showed more cases of AP in endodontically treated teeth.